Evaluation of toxic heavy metals content in traditional medicine from east coast region, Malaysia - Khalid, Reem Saadi (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2013)
Traditional medicine (TM) is the oldest form of health care style known to humanity; it has been used in different cultures throughout the history. According to the World Health Organization (WHO) reports, more than 70% of the world population use TM. The broad use of TM is often attributed to the accessibility, affordability and availability of such products to the majority of the world's population. Asians are well-known for their reliance on TM. Malaysia has a long tradition and rich legacy from three main cultural groups (Malay, Chinese and Indian) of using TM, a large section of the population in this country is depending on TM for their healthcare needs. The huge demand for TM in Malaysia has significantly increased the Malaysian TM market from US$ 385million in 2000 to US$ 1.29 billion in 2005. Due to the global wide diffusion of TM the safety, efficacy and quality control of such products became significant concern from various health institutes. Presence of toxic substances such as heavy metals is often reported in TM products. This study has been initiated with a prime focus of detecting the amount of heavy metals namely arsenic (As), cadmium (Cd), lead (Pb), nickel (Ni), zinc (Zn) and iron (Fe) in locally available traditional medicines both registered and unregistered medicinal products in various dosage forms from the East Coast region of Malaysia. The determination of Zn and Fe were conducted using Flame Atomic Absorption Spectrometer (FAAS), while Pb, Cd and Ni analysis were conducted using Graphite Furnace Atomic Absorption Spectrometer (GFAAS) and As detection was performed with Hydride Generation Atomic Absorption Spectrometer (HGAAS).TM samples were collected from three states of Malaysia namely Pahang, Terengganu and Kelantan. Total of sixty TM samples from various dosage forms such as capsule (50%), pill (25%), powder (21.6%) and tablet (3.4%) were analysed to determine the content of heavy metal using AAS. Three different acid digestion methods were compared to optimize the best sample preparation technique for analyzing TM samples. They were nitric –perchloric acid digestion (Method-A) nitric acid digestion (Method-B) and hydrochloric –nitric acid (Method-C) digestion respectively. It was found that Method-C showed the highest recovery compared to the other two methods (Method-A and Method-B) and the difference was found statistically significant (p< 0.05). Method validation was performed using QC standard sample, spiked TM samples and standard reference material (SRM). It was found that the limit of detection (LOD) for As, Cd, Pb, Ni, Zn and Fe were 0.11ppb, 0.1ppb, 1.17 ppb, 2.01 ppb, 0.01 ppm and 0.09 ppm respectively. Limit of quantification (LOQ) were 1.1 ppb for As, 1ppb for Cd, 11.7 ppb for Pb, 20.1 ppb for Ni, 0.1 ppm for Zn and 0.9 ppm for Fe. The recovery percentages for QC samples were ranged from 95.12- 102.4 which reflects the accuracy of the method. While the relative standard deviation (RSD) that represents the precision of the method for QC samples were in the range of 3.23-0.2. For spiked TM samples the recovery range and the RSD range were 95- 105 and 0.11-5.0 respectively. All the validation results were within the specification limit of American Organization of Analytical Chemistry (AOAC) guideline. The accuracy of the method was further checked by the analysis of SRM. The recovery percentages of all metals were in the range of 94.5-108. Among the sixty TM samples it was found that As, Cd, Pb, Ni, Zn and Fe were present in 43%, 81%, 90%, 100%, 100% and 93% of the total samples with a concentrations range of 0.214-1.325, 0.1-1.23, 1.2-19.3, 2.01-36.3, 13.2- 391 and 103.3- 1484.7 μg/g respectively. The results further revealed the fact that 36 % of samples contain Cd higher than the permissible limit and 10% of the samples were found having Pb above the permissible limit set by NPCB.